Pemberdayaan Ekonomi Masyarakat Desa Sandey Konawe Selatan Melalui Pengembangan Batako Interlock Abu Sekam Padi: Penelitian - Edward Ngii; La Welendo; Ridwan Syah Nuhun; Muammar Makmur; Rini Sriyani; Fikri Aris Munandar; Slamet (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sandey Village, Angata District, South Konawe has rice husk waste potential reaching 390 tons per year that has not been optimally utilized. On the other hand, SME "Zidan Roster" as a brick craftsman faces problems of high production costs (IDR 900,000/truck of conventional materials) and product quality that does not meet SNI standards. The purpose of this activity is to transfer rice husk ash-based interlocking block technology to improve economic efficiency and address environmental problems. The implementation method uses a "Technology Transfer and Community Empowerment" approach through five stages: preparation and baseline assessment, laboratory trials, technology transfer and implementation, evaluation and product testing, and consolidation and sustainability. Based on previous research results, the optimal formula used is: cement 30%, sand 35%, rice husk ash 35%, with water-cement ratio of 0.5. Results show that interlocking block products meet SNI standards with compressive strength of 26.5 kg/cm² and water absorption of 25%. Monitoring and evaluation showed that 90% of partners mastered BATASIK (Rice Husk Ash Interlocking Block) production skills. Economic impacts include 30-40% production cost efficiency and 25-30% income increase. Environmental impacts include rice husk waste utilization and CO₂ emission reduction. This program successfully created a sustainable community empowerment model through environmentally friendly technology innovation.